Srategi Pengelolaan Kelas Dalam Meningkatkan Prestasi Belajar Siswa Di Madrasah Aliyah: Studi Kasus Di Madrasah Aliyah Negeri Ngrambe Ngawi - Wibawati Bermi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2017)
The aimofthis study istodescribe â€œThe Strategies of Classroom Management for improving Studentsâ€™ Achievementâ€. Teacher as a manager of learning activities in the classroom has recognized as oneofcrucial impact to improve student sachievement. Professional teachers are not only demanded by mastering material of the lesson but also the teachers are demanded to manage the classroom properly by creating and maintainin the condition of learning process qualify, in order to the aim of learning process achieves. There for e,consideration of governmentâ€™seffort to increase the quality atalllevels of education is going well. The implementation of classroom management strategies for learning process is one of solution to solve the fundamental issues of educationâ€™s problem in Indonesia.